A synopsis of the orchid weevil genus Orchidophilus Buchanan (Curculionidae, Baridinae), with taxonomic rectifications and description of one new species - Prena, Jens (Zootaxa, 2008)
Six species of the weevil genus Orchidophilus Buchanan are recognized: O. epidendri (Murray) comb. n. (=Acythopeus genuinus Pascoe syn. n., =Baris orchivora Blackburn syn. n., =Apotomorhinus orchidearum Kolbe syn. n.), O. aterrimus (Waterhouse), O. eburifer (Pascoe) comb. n. (=Acythopeus gilvonotatus Barber syn. n.), O. peregrinator Buchanan, O. ran Morimoto and O. insidiosus Prena sp. n. These species appear to be native to Indonesia, Malaysia, the Philippines and Singapore but are dispersed frequently with orchid cultivars by global trade. Orchidophilus aterrimus has been intercepted most frequently and now is established in several Indo-Pacific regions outside its native range. Nearly as common as, and occasionally confused with, the former is O. epidendri. Orchidophilus ran is of some significance in Japan and Korea, while O. peregrinator, O. eburifer and O. insidiosus were intercepted occasionally at scattered locations before 1970. An identification key for the six species is provided. Lectotypes are designated for Baridius aterrimus Waterhouse, Acythopeus genuinus Pascoe, Baris orchivora Blackburn and Apotomorhinus orchidearum Kolbe; a neotype is designated for Centrinus epidendri Murray.